2014
DOI: 10.4103/0972-5229.142179
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene compliance among healthcare workers in an accredited tertiary care hospital

Abstract: Aim:We are using multimodal technique to improve hand hygiene (HH) compliance among all health care staff for the past 1-year. This cross-sectional observational study was conducted in the surgical ICU to assess adherence to HH among nurses and allied healthcare workers, at the end of the training year.Materials and Methods:This was a cross-sectional observational study using direct observation technique. A single observer collected all HH data. During this analysis, 1500 HH opportunities were observed. HH com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 9 publications
(19 reference statements)
3
35
1
Order By: Relevance
“…In addition, the same study pointed out that several professionals worked below standard conditions during the observation periods. This reality was also reported in another study, which noted that the unavailability of materials in the work area, the high workload, and the shortage of nurses were barriers to professionals' adherence (8) . Teker et al (9) listed multiple factors with the potential to influence these indicators, such as lack of training and experience; lack of feedback on inadequate performance; working in highly complex care units; inadequate staffing; lack of role models in the team; inadequate use of gloves; lack of knowledge about the importance of the procedure; inadequate time management; planning of care without accounting for the time necessary for hand hygiene; lack of motivation at individual and institutional levels; lack of priority of hand hygiene at the institutional level; lack of performance rewards or sanctions; and lack of institutional guidelines.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In addition, the same study pointed out that several professionals worked below standard conditions during the observation periods. This reality was also reported in another study, which noted that the unavailability of materials in the work area, the high workload, and the shortage of nurses were barriers to professionals' adherence (8) . Teker et al (9) listed multiple factors with the potential to influence these indicators, such as lack of training and experience; lack of feedback on inadequate performance; working in highly complex care units; inadequate staffing; lack of role models in the team; inadequate use of gloves; lack of knowledge about the importance of the procedure; inadequate time management; planning of care without accounting for the time necessary for hand hygiene; lack of motivation at individual and institutional levels; lack of priority of hand hygiene at the institutional level; lack of performance rewards or sanctions; and lack of institutional guidelines.…”
Section: Discussionmentioning
confidence: 83%
“…However, one of the studies reported that, despite the higher levels of training, only 43% of nurses and 18% of health technicians had washed their hands during the observation period, which may suggest that the knowledge about a certain procedure does not, in itself, translate into best practices (6) . On the other hand, in a study that compared nurses and allied healthcare workers, the adherence to hand hygiene was of 63% among nurses and 86.5% among allied healthcare workers (8) . Contrary to these results, one of the analyzed studies (10) found that adherence was higher among nurses (50%) than among doctors (45%) and other health professionals (38.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have found sex of the respondents, duration of practice, water supply, availability of disposable hand towels, patient load and proximity of hand washing facility as potent determinants of hand hygiene practice. [3,10,[12][13][14][15] …”
Section: Discussionmentioning
confidence: 99%